Method of Building Signaling Big Data Real-Time Query Platform Based on Hadoop - 陈丽; 王锐 (Dianxin kexue)
With the popularity of 4G communication technology，and development of mobile internet application，the data flow is booming，and traditional processing method is difficult to support the massive signalling data real-time query requirement.Therefore，a kind of data real-time query platform based on Hadoop was put forward，to support the details of a single large scale signaling processing.Through data collection，data modeling，rowkey design，data compression and storage，etc.，real-time data query service was provided.Finally，the experimental environment of the current network was verified，which could get very good income.